Aktivitas Ekstrak Daun Nangka (Artocarpus heterophyllus L.) Terhadap Bakteri Staphylococcus epidermidis - Sri Wahyu Vita; Putri Vidiasari Darsono; Saftia Aryzki (BIOEDUSCIENCE, 2022)
Background: Acne is an infectious disease that is still a severe problem. The therapy used for acne is the bacterial antibiotic Clindamycin. Still, there is a lot of resistance to these antibiotics, one of which is Staphylococcus epidermidis, so it is necessary to find alternative antibacterial drugs to treat acne. Non-pharmacological therapy often used is jackfruit leaf extract (Artocarpus heterophyllus L.) which contains secondary metabolites such as flavonoids, saponins, and tannins, which are thought to be effective as antibacterial agents. Methods: The type of research used is True Experimental with the Posttest-Only Control Group research design. The research method used healthy diffusion and liquid dilution, and then the data were analyzed using ANOVA. Results: It was found that jackfruit leaf extract (Artocarpus heterophyllus L.) had antibacterial activity against Staphylococcus epidermidis with a diameter of inhibition zone at a concentration of 50 ppm of 11.7 mm, a concentration of 75 ppm of 12.1 mm, a concentration of 100 ppm of 12.3 mm and had a minimum inhibitory ability at a concentration of 50 ppm with a p-value of 0.007 in the Kruskall-Wallis Test and the Mann Whitney Test showed a p-value of 0.025. Still, the extract did not have the minimum killing ability. Conclusions: Jackfruit leaf extract can only inhibit the growth of Staphylococcus epidermidis bacteria but cannot kill the growth of these bacteria.